2021
DOI: 10.3389/fsens.2021.657931
|View full text |Cite
|
Sign up to set email alerts
|

Review: Influences of Semiconductor Metal Oxide Properties on Gas Sensing Characteristics

Abstract: Semiconductor metal oxides (SMOxs) are widely used in gas sensors due to their excellent sensing properties, abundance, and ease of manufacture. The best examples of these sensing materials are SnO2 and TiO2 that have wide band gap and offer unique set of functional properties; the most important of which are electrical conductivity and high surface reactivity. There has been a constant development of SMOx sensor materials in the literature that has been accompanied by the improvement of their gas-sensitive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(98 citation statements)
references
References 210 publications
(261 reference statements)
1
97
0
Order By: Relevance
“…This change of baseline occurs due to additional water molecules interacting with the adsorbed oxygen ions on the active sites of the sensing surface, through hydrogen ions (H+) and hydroxyl ions (OH−) [30,31]. This is particularly critical when detecting VOCs (reducing gas), as the water molecules interact with the MOX material and release the captured electrons [32]. As a result, the baseline resistance decreases with increasing humidity; therefore, we see the baseline resistance of both sensors at 90% r.h. to be lower than that at 40% r.h.…”
Section: Resultsmentioning
confidence: 99%
“…This change of baseline occurs due to additional water molecules interacting with the adsorbed oxygen ions on the active sites of the sensing surface, through hydrogen ions (H+) and hydroxyl ions (OH−) [30,31]. This is particularly critical when detecting VOCs (reducing gas), as the water molecules interact with the MOX material and release the captured electrons [32]. As a result, the baseline resistance decreases with increasing humidity; therefore, we see the baseline resistance of both sensors at 90% r.h. to be lower than that at 40% r.h.…”
Section: Resultsmentioning
confidence: 99%
“…ture [24]. Different literature reports have shown that the gas response at low temperatures starts to disappear at around 200 °C and is replaced by the typical sensitivity response at high temperatures [13,20]. The optimum temperature depends on the sensing material and the sensed gas.…”
Section: Co Analysismentioning
confidence: 99%
“…One of them is that the type of oxygen species adsorbed on the oxide depends on temperature [28]. As mentioned, atomic species, which are more reactive than molecular species, predominate at temperatures above 150 • C [13]. Another fact is that the oxidation reaction is an activated process, where its rate increases with temperature.…”
Section: Co Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, this process ends up in electron trapping from the valence band, which successively increases the concentration of holes near the surface. This explains why, in general, p-type materials exhibit lower electrical resistance in air when compared to n-type ones [18]. In spite of the technological importance of NiO material, the understanding of the gas-sensing mechanism involved in the detection of different types of gases continues to be in progress.…”
Section: Introductionmentioning
confidence: 99%